Cannabis‐based medicines and medical cannabis for patients with neuropathic pain and other pain disorders: Nationwide register‐based pharmacoepidemiologic comparison with propensity score matched controls. (16th October 2021) - Hjorthøj, Carsten; La Cour, Peter; Nordentoft, Merete; Posselt, Christine Merrild
Abstract: Background: Neuropathic pain and other pain disorders have received attention as potential indications for use of cannabis‐based medicines or medical cannabis (CBM/MC). Evidence regarding the efficacy and safety of CBM/MC for pain disorders is, however, insufficient. Denmark introduced a pilot programme of medical cannabis in January 2018. We aimed to evaluate efficacy, safety, and non‐specific effects of CBM/MC used under the pilot programme compared with controls. Methods: We conducted a nationwide register‐based cohort study in Denmark, identifying all individuals redeeming at least one prescription for CBM/MC for either neuropathic pain ( n = 1817) or other and unspecified pain disorders ( n = 924), and to match one control to each case using propensity score matching. Results: Among both patient groups, users of THC used more opioids during follow‐up than controls. Among patients with neuropathic pain, however, users of either CBD, THC, or combined CBD + THC used less gabapentin than controls. Users of all three classes of CBM/MC were hospitalized fewer days than controls among neuropathic‐pain patients but not among patients with other or unspecified pain disorders. Conclusions: CBM/MC were generally safe and even displayed some positive effects among patients with neuropathic pain. We conclude that CBM/MC are safe and possibly efficacious for patients with neuropathic pain but not patients with other pain disorders. Significance: Patients with neuropathic pain may benefit from treatment with cannabis‐based medicines or medical cannabis (CBM/MC), particularly in terms of reduced use of gabapentin and fewer days admitted to hospitals, compared with propensity score matched controls. CBM/MC did not, however, reduce the use of opioids. We did not find evidence that CBM/MC were effective for patients with other pain disorders.